Enhancing Corporate Governance Through Rigorous and Insightful Auditing Processes - Amalia, Gita (Yayasan Pendidikan Bukhari Dwi Muslim, 2024)
Purpose: This research investigates the relationship between the audit process and improved corporate governance practices in organizations. The focus is on assessing the effectiveness of the audit process in ensuring transparency, accountability, and integrity of company operations. Research Design and Methodology: This study utilized a quantitative descriptive approach. Data was collected through an extensive literature review covering academic journals, books, reports, and relevant publications from trusted organizations. The literature review process systematically identified, reviewed, and synthesized relevant sources. Findings and Discussion: The findings suggest that auditor independence, competence, and rigor are fundamental pillars supporting audit practices' credibility and reliability. Regulatory oversight mechanisms, including audit committees and regulatory bodies, are essential in maintaining audit standards and promoting governance integrity. Audit quality, ethics, and regulatory compliance remain vital concerns that require collaborative efforts among policymakers, regulators, auditors, and corporate practitioners. These findings highlight the importance of continuous professional development for auditors to deal with the evolving business landscape and complexity of financial transactions. Implications: The practical implications of this research include recommendations to strengthen audit processes and governance mechanisms through enhanced continuous professional training for auditors, the application of advanced technologies such as data analytics and artificial intelligence, and collaboration between stakeholders to promote transparency and accountability in audit practices. The research also underscores the need for regulatory reforms responsive to evolving market dynamics to improve supervisory effectiveness and regulatory compliance